Propozycje „Ethosu” - MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2024)
Propozycje "Ethosu. Kwartalnika Instytutu Jana Pawła II KUL": H. Teke, Increasing Ethical Awareness: The Enhancement of Long-term Effects of Ethics Teaching; A Quantitative Study, Lund University, Lund 2019.